A Growing Concern: The Emergence and Dissemination of Carbapenemase-producing Enterobacterales (CPE) in Canada. (October 2020) - Mitchell, Robyn; Mataseje, Laura; Boyd, David; Al-Rawahi, Ghada; Davis, Ian; Ellis, Chelsey; Embree, Joanne; Hota, Susy; Kibsey, Pamela; Maisonneuve-Rosemont, pital; Leis, Jerome; McGeer, Allison; et al.
Abstract : Background: Carbapenemase-producing Enterobacterales (CPE) have rapidly become a global health concern and are associated with substantial morbidity and mortality due to limited treatment options. Travel to endemic areas, especially healthcare exposure in these areas, is an important risk factor for acquisition. We describe the evolving epidemiology, molecular features, and outcomes of CPE in Canada through surveillance by the Canadian Nosocomial Infection Surveillance Program (CNISP). Methods: CNISP has conducted surveillance for CPE among inpatients and outpatients of all ages since 2010. Participating acute-care facilities submit eligible specimens to the National Microbiology Laboratory for detection of carbapenemase production, and epidemiological data are collected. Incidence rates per 10, 000 patient days are calculated based on inpatient data. Results: In total, 59 CNISP hospitals in 10 Canadian provinces representing 21, 789 beds and 6, 785, 013 patient days participated in this surveillance. From 2010 to 2018, 118 (26%) CPE-infected and 547 (74%) CPE-colonized patients were identified. Few pediatric cases were identified (n = 18). Infection incidence rates remain low and stable (0.02 per 10, 000 patient days in 2010 to 0.03 per 10, 000 patient days in 2018), and colonization incidence rates have increased by 89% over the surveillance period. Overall, 92% of cases were acquired in a healthcare facility: 61% (n = 278) in a Canadian healthcare facility and 31% (n = 142) in a healthcare facility outside Canada. Of the 8% of cases not acquired in a healthcare facility, 50% (16 of 32) reported travel outside of Canada in the 12 months prior to positive culture. The distribution of carbapenemases varied by region; New Delhi metallo- B -lactamase (NDM) was dominant (59%) in western Canada and Klebsiella pneumoniae carbapenemase (KPC) (66%) in central Canada. NDM and class D carbapenemase OXA-48 were more commonly identified among those who traveled outside of Canada, whereas KPC was more commonly identified among patients without travel. In addition, 30-day all-cause mortality was 14% (25 of 181) among CPE infected patients and 32% (14 of 44) among those with bacteremia. Conclusions: CPE rates remain low in Canada; however, national surveillance data suggest that the increase in CPE in Canada is now being driven by local nosocomial transmission as well as travel and healthcare within endemic areas. Changes in screening practices may have contributed to the increase in colonizations; however, these data are currently lacking and will be collected moving forward. These data highlight the need to intensify surveillance and coordinate infection control measures to prevent further spread of CPE in Canadian acute-care hospitals. Funding: None Disclosures: Susy Hota reports contracted research for Finch Therapeutics. Allison McGeer reports funds to her institution for projects for which she is the principal investigator from Pfizer and Merck, as well as consulting fees from the following companies: Sanofi-Pasteur, Sunovion, GSK, Pfizer, and Cidara.